Control Air Pollution to The Sustainable Development Goals Vietnam Perspective - Le Thi Thao; Phan Vinh Tuan Anh (Administrative and Environmental Law Review, 2023)
The trend of globalization has brought great opportunities, creating favorable conditions for all countries in the world to promote and successfully implement the socio-economic growth goals set out. However, it also poses many challenges in protecting and preserving the natural living environment, which naturally plays the role of external conditions to create and maintain the life and development of humans and creatures. The process of industrialization and modernization has been strongly promoted, leading to a severe decline in the function and usefulness of environmental components in cities around the world and Vietnam. Many countries have taken systematic regulatory actions against air pollution. The method used in this research is the normative juridical method. The normative juridical method is a method using secondary data such as the law and regulations in force in Vietnam, especially those related to air pollution and suitable developments. The authors clarify the point of view on the current state of Vietnamese legislation on air pollution control. Existing issues in the polluted-air controlling policy are clarified. The study's results so that improving the law on control, management, technical regulations on air pollution control, responsibilities of relevant agencies and sanctions for polluting acts proposed air pollution in order to prevent and limit “barriers” towards the goal of sustainable development.